If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -13 = 31 Reorder the terms: -13 + 9x = 31 Solving -13 + 9x = 31 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 9x = 31 + 13 Combine like terms: -13 + 13 = 0 0 + 9x = 31 + 13 9x = 31 + 13 Combine like terms: 31 + 13 = 44 9x = 44 Divide each side by '9'. x = 4.888888889 Simplifying x = 4.888888889
| 4x+9=6x+7 | | 25k^4-1=0 | | -4(-12-15b)=-5(-12b-12) | | 5x-20=3(x-4) | | -7p=42 | | -5/2(w-1)+3=18 | | X-4-3x=-2x-4 | | b-4=3b | | 12=-3v+6b | | -7(-2g+4)+19=-9+14g | | 3(n-4)=-42 | | 9(2X+5)=3X | | 1x+2=4x-12 | | 11-4c=3 | | 3(x-14)+(x+30)/5=x+2(3x-15)/5 | | (x+7)(2x-3)=140 | | 7x+1=8-4x | | -45+8v=-3(1+10v)-4v | | -10+14u=-8(-3u+15) | | x+2x+x-12=180 | | 25=4.5+12 | | -(-10t+2)+6=8-3t | | -3(-10-4s)=-2(-15-6s) | | 0=n-1-3 | | 21=15+4(m-2) | | Y(3x-4)=3(x-2) | | 10+x=4x+2x | | -6x+5=-94+5x | | 3(16m+13)=9+8(6m+9) | | 6=-2n-6(3n+2) | | 36y^3-9=y-324y^2 | | -1+2b=2-3b+2b |